Incentives and Job Satisfaction’s Effects on Trio Batanghari Foundation Teachers’ Work Productivity - Ansori, Ansori; Faruq, Muhammad Shoffa Saifillah Al; N., Yennizar; Zainuddin, Zainuddin; Armitha, Invia Dyah (International Journal Labs, 2022)
Based on the initial Grand Tour, it turns out that there are still some teachers who are not satisfied with the incentives received, there are no teachers who excel in academic or non-academic fields, and there are no teachers who have participated in the outstanding teachers’ event at the Trio Batang Hari Foundation. This research aims to measure the effect of incentives and job satisfaction on teachers’ work productivity in the Trio Batanghari Foundation. This study uses a quantitative method, with a quantitative approach. The population of this research is all teachers or workers at the Trio Batang Hari Foundation as many as 38 teachers. The data analysis used is multiple regression analysis and the data is processed with the help of the SPSS Version 22.0 program. The results showed, partially, incentives have a significant effect on teacher work productivity at the Trio Batang Hari Foundation by 42.5% calculation tcount>ttable (2,313>1,686), which means that there is a significant influence between incentives and teacher work productivity. Job satisfaction on teacher work productivity is 47% in the calculation of tcount> ttable (3,014>1,686), this means that there is a significant influence between job satisfaction and teacher work productivity. Incentives and job satisfaction have a simultaneous effect on teacher work productivity as much as 42.1% in the calculation fcount>ftable (12.717>3.24) that reject Ho and accept Hi. There is a significant influence between incentives and job satisfaction have a simultaneous effect on teacher work productivity.